2021
DOI: 10.3746/pnf.2021.26.2.200
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties and Protective Effects of Aerial Parts fromCnidium officinaleMakino on Oxidative Stress-Induced Neuronal Cell Death

Abstract: The rhizomes of Cnidium officinale Makino have been used as a traditional medicine for many purposes, however, use of its aerial parts is very limited. We investigated the antioxidant properties and protective effects of the aerial parts (leaves and stems) from C. officinale on H2O2-induced toxicity in SH-SY5Y neuroblastoma. C. officinale methanol extracts (70%) were sequentially fractionated using hexane (non-polar fraction, NF), ethyl acetate (intermediate polar fraction, IF), and water (polar fraction, PF).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Inula britannica var. chinensis were prepared with different solvents and it was reported that the water fraction showed the strongest antioxidant activity (DPPH IC50 20.7 µg/mL; ABTS IC50 39.4 µg/mL) [30].The total phenolic content of methanol, ethanol, water, and ethyl acetate extracts obtained by the Folin-Ciocalteu technique from the aerial parts of I. helenium species growing in Turkey ranged from 4.18 to 102.91 mg gallic acid equivalent/g dry extract [31].In another study, it was reported that the total amount of phenol in the chloroform and ethyl acetate extracts of I. helenium root was 5.06±0.06 (mg gallic acid g -1 ) and 42.2±0.07 (mg gallic acid g -1 ), respectively [32].Chahmi et al assessed the antioxidant activity, total phenolic content, and flavonoid content of ethanol and ethyl acetate extracts of aerial parts of I. viscosa collected from three Moroccan regions, finding that the ethanol extract from Sefrou had the highest antioxidant capacity (274.39±6.94 mg gallic acid equivalent/g dry extract), probably due to its high polyphenol concentration. [33].…”
Section: Discussionmentioning
confidence: 99%
“…Inula britannica var. chinensis were prepared with different solvents and it was reported that the water fraction showed the strongest antioxidant activity (DPPH IC50 20.7 µg/mL; ABTS IC50 39.4 µg/mL) [30].The total phenolic content of methanol, ethanol, water, and ethyl acetate extracts obtained by the Folin-Ciocalteu technique from the aerial parts of I. helenium species growing in Turkey ranged from 4.18 to 102.91 mg gallic acid equivalent/g dry extract [31].In another study, it was reported that the total amount of phenol in the chloroform and ethyl acetate extracts of I. helenium root was 5.06±0.06 (mg gallic acid g -1 ) and 42.2±0.07 (mg gallic acid g -1 ), respectively [32].Chahmi et al assessed the antioxidant activity, total phenolic content, and flavonoid content of ethanol and ethyl acetate extracts of aerial parts of I. viscosa collected from three Moroccan regions, finding that the ethanol extract from Sefrou had the highest antioxidant capacity (274.39±6.94 mg gallic acid equivalent/g dry extract), probably due to its high polyphenol concentration. [33].…”
Section: Discussionmentioning
confidence: 99%
“…At a concentration of 25-200 μg/mL, IF also significantly reduces the level of intracellular reactive oxygen species by 7.72-47.47 %. [7] Compare the scavenging activities of TEAC, ORAC, DPPH and other free radicals from the 80 % methanol extracts of COM and Ligusticum chuanxiong Hort. The results show that both have similar and strong antioxidant activity.…”
Section: Antioxidant Activitiesmentioning
confidence: 99%
“…[5] COM is also used in other aspects such as diet, its stem and root are devoted to drinks, bread, candy, alcohol, salad, and its leaves can be employed to rice packaging and seasoning vegetables. [4,[6][7] Acaricidal activity, butylidene phthalide and other effective ingredients in CR can remove acaroid mites and rotten anteater mites. [8][9] Adulticidal activity, phthalides and alkyl phthalide derivatives in CR can kill drosophila melanogaster, B-and Q-biotypes of bemisia tabaci.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations